(untitled) (2020)
This article is an attempt to establish the effectiveness of the creation of an intended environment for foreign language learning in order to diminish the passive approach of listening and speaking skills of students in communes 1 and 2 of Bucaramanga-Colombia; supporting inclusion from the curriculum, through multichannel stimulation and the implementation of strategies for meaningful learning. The quantitative research design was configured by setting two groups: a control group and an experimental one with students from an institution that assists population in vulnerable situations. In the experiment, a Manova analysis was performed taking into consideration the results of a pre-test and a post-test for listening and speaking skills, establishing correlations with the perception channels characterized for each of the students in both groups. A significant difference was achieved (Traza Pillai p <0.05) for the variable listening skill between the control group and the experimental group, with the last one being higher. There was a tendency to show significant differences in speaking ability (p = 0.062). Effective strategies are the ones that encourage language interaction in context, collaborative learning, comprehensible input, the reduction of students’ anxiety as well as their active and self-directed participation.